Development of a clinical laboratory data base of hyper and hypo alpha lipoproteins in Campinas-SP and neighboring region Construção de um banco de dados clínico laboratorial de hiper e hipoalfalipoproteinêmicos em Campinas-SP e região - Eliane Soler Parra; Vanessa Helena de Souza Zago; Natália Baratella Panzoldo; Fernanda Alexandre; Felipe Vendrame; Vitor Wilson de Moura Virginio; Isabela Calanca Vieira; Marcelo Scarpari Dutra Rodrigues; Angela de Souza Cassol; Fabio D'Alexandri; Vera Sylvia Castanho; Rui Nakamura; et al. (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: The development of research for diagnosis, prevention and treatment of atherosclerotic cardiovascular disease is of utmost importance due to the fact that it is the main cause of morbidity and mortality in Brazil. OBJECTIVE: To demonstrate the phases of the selection process for candidates with the aim to develop a clinical-laboratorial database of hyper alpha lipoproteinemic patients (hyper A) - high density lipoprotein cholesterol (HDL-C) ≥ 68 mg/dl) and hypo alpha lipoproteinemic patients (hypo A) - HDL-C < 39 mg/dl. MATERIAL AND METHODS: The volunteers were contacted after selection of lipid profiles from individuals treated at the Sistema Único de Saúde (SUS), Campinas-SP and neighboring area. Afterwards, the selected patients went through blood collection, clinical examinations and answered questionnaires on dietary frequency and physical activity. After this preliminary evaluation, some individuals were convened to another blood collection and, subsequently, were submitted to an ultrasonographic exam of the carotid arteries. RESULTS: Only 0.6% and 0.3% from 598,288 lipid profiles were selected for hyper A and hypo A groups, respectively, including gender disparity. Lack of effective questionnaires (75%), missing calls (60%) and non-inclusion were the major hindrances in the construction of this database. DISCUSSION: The difficulties to obtain eligible candidates were also due to the low prevalence of both groups hypo A and hyper A and the high prevalence of pathologies that contribute to non-genetic variations of HDL-C. CONCLUSION: In spite of the obstacles in the development of this database, this study brought about several scientific publications. Furthermore, the development of molecular analyzes and functionality will shortly generate other findings, contributing to the diagnosis and follow-up of HDL dyslipidemias. INTRODUÇÃO: O desenvolvimento de pesquisa para diagnóstico e prevenção da doença aterosclerótica cardiovascular no Brasil é de grande importância por esta ser a principal causa de morbimortalidade no país. OBJETIVO: Demonstrar as etapas do processo de seleção de voluntários para a construção de um banco de dados clínico-laboratorial de indivíduos hiperalfalipoproteinêmicos (hiper A) - colesterol da lipoproteína de alta densidade (HDL-C) ≥ 68 mg/dl - e hipoalfalipoproteinêmicos (hipo A) - HDL-C < 39 mg/dl. MATERIAL E MÉTODOS: Os voluntários são contatados a partir de resultados de perfis lipídicos de indivíduos atendidos pelo Sistema Único de Saúde (SUS) de Campinas-SP e região e, se selecionados, são convidados para coleta de sangue, exames clínicos e responder a questionários de atividade física e de frequência alimentar. Após essa avaliação, os indivíduos podem ser convocados para nova coleta de sangue e, posteriormente, para a ultrassonografia de carótidas. RESULTADOS: Entre 598.288 perfis lipídicos recebidos das redes públicas, apenas 0,6% e 0,3% compuseram os nossos grupos hiper A e hipo A, com disparidade entre os gêneros. A falta de questionários efetivos (75%), das chamadas não atendidas (60%) e a não inclusão foram os pontos mais difíceis na construção do banco de dados. DISCUSSÃO: A dificuldade de obtenção de voluntários elegíveis também se deve à baixa prevalência de hipo A e hiper A e à alta prevalência de patologias que contribuem para variações não genéticas do HDL-C. CONCLUSÃO: Apesar das dificuldades na criação da base de dados, este estudo gerou várias publicações e, com o desenvolvimento das análises moleculares e da funcionalidade, muitas outras seguirão em curto período, fatos contribuintes para o diagnóstico e o acompanhamento das dislipidemias envolvendo a HDL.